Assessment of intrusive and non-intrusive non-deterministic CFD methodologies based on polynomial chaos expansions. (1st March 2010) - Dinescu, Cristian; Smirnov, Sergey; Hirsch, Charles; Lacor, Chris
The paper presents the computational results of an ongoing validation effort of two polynomial chaos methods used in the non-deterministic simulations of the transonic flow in the NASA Rotor 37 axial compressor. In the first stage, a code to code comparison on the geometry of the NASA Rotor 37 allows exploring different influences on the computed mean and standard deviation of the pressure field and output functionals of interest as the inlet mass flow rate, the isentropic efficiency and the pressure ratio. The validation results are concerned with the management of two uncertainties: one of operational origin imposed on the outlet static pressure boundary condition and another one of geometrical nature the tip clearance particularly. These results are displayed as non-deterministic compressor maps and graphs showing the dependency of the functionals' coefficients of variations with respect to the inlet mass flow rate. Finally, our conclusions on the employed computational programme are drawn.